Redox Imbalance in Inflammation: The Interplay of Oxidative and Reductive Stress - Francesco Bellanti; Anna Rita Daniela Coda; Maria Incoronata Trecca; Aurelio Lo Buglio; Gaetano Serviddio; Gianluigi Vendemiale (Antioxidants, 2025)
Redox imbalance plays a pivotal role in the regulation of inflammation, influencing both the onset and progression of various inflammatory conditions. While the pro-inflammatory role of oxidative stress (OS) is well established, the impact of reductive stress (RS)—a condition marked by excessive reducing equivalents such as NADH, NADPH, and reduced glutathione (GSH)—remains underappreciated. This review offers a novel integrative perspective by analyzing how OS and RS act not merely in opposition, but as interconnected modulators of immune function. We explore the mechanisms through which OS activates inflammatory pathways, and how RS, when sustained, can paradoxically impair immune defense, alter redox-sensitive signaling, and contribute to disease progression. Emphasis is placed on the dynamic interplay between these redox extremes and their combined contribution to the pathogenesis of chronic inflammatory diseases, including autoimmune, cardiovascular, and neuroinflammatory disorders. Additionally, we evaluate therapeutic strategies that target redox homeostasis, arguing for a shift from antioxidant-centric treatments to approaches that consider the bidirectional nature of redox dysregulation. This framework may inform the development of more precise interventions for inflammation-related diseases.